Analytical study of the economic effects of sports for seniors in Iran - Ahmadi, Lida Moazen; Devin, Hassan Fahim; Mirzazadeh, Zahrasadat; Peymanizad, Hossein (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to analyze the economic effects of elderly sports in Iran. The present study was qualitative. The research is based on grounded theory applying the emerging method attributed to Glaser (1992). Professors, of sports management, sociology, psychology, municipal managers and researchers (with at least two scientific research articles in the field of research) constituted the population of the current study. Since the purpose of qualitative sampling is information saturation, the combined theoretical sampling method of the improbably purposeful type was used until the theoretical saturation was achieved. A total of 15 participants were recruited as sample for the present study. Acceptability, transferability and verifiability indices were used to determine validity. In order to evaluate the reliability of the interviews, the method of intra-subject agreement of two coders (evaluators) was used. Findings of the present study revealed that the mean age of the research participants was 48 years. Out of all, 75% participants were males. The average career background of the participants was 22.5 years and 80% of them held a Ph.D. degree. The results showed that the economic effects of elderly sports were divided into two categories: micro and macro. The macro level consisted of the two concepts of increasing GDP (5 signs) and private sector investment (3 signs). The micro level consisted of the two concepts of quantitative and qualitative improvement of production inputs (6 signs) and reduction of treatment costs (8 signs).